Carbamazepine-Induced Juvenile Myoclonic Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The risk of aggravation of juvenile myoclonic epilepsy (JME) among 40 of 170 consecutive patients who had received carbamazepine (CBZ) or phenytoin (PHT) was determined at the Centre Saint Paul, Marseille, and the Clinique Neurologique, Hopital Pasteur, Nice, France.